A Two-Dimensional (2D) Potential Distribution Model for the Short Gate-Length Ion-Implanted GaAs Mesfets Under Dark and Illuminated Conditions - Shweta Tripathi; S. Jit (Журнал нано- та електронної фізики)
An analytical 2D model to predict the potential distribution of short-channel ion-implanted GaAs MESFETs has been presented. The 2D potential distribution in the channel of the short-channel device has been obtained by solving the 2D Poisson’s equation in conjunction with suitable boundary conditions using superposition method. The remarkable feature of the proposed model is that the implanted doping profile has been treated in completely analytical manner. A double-integrable Gaussian-like function has been assumed as the doping distribution profile in the vertical direction of the channel. The effects of excess carrier generation due to the incident optical radiation in channel region have been included in the Poisson’s equation to study the optical effects on the device. The photovoltage developed across the gate metal has also been modeled. The proposed model has been verified by comparing the theoretically predicted results with simulated data obtained by using the commercially available ATLASTM2D device simulator.